CLINICAL PROTOCOLS ADOPTED BY NURSES IN THE EXTRAVASATION OF ANTINEOPLASTIC DRUGS: AN INTEGRATIVE REVIEW - Silva, José Kaique Marques da (2024)
Objective: To identify the patient safety measures and clinical protocols adopted by nurses in the case of antineoplastic extravasation. Methodology: The research approach was based on an integrative literature review that used the PICo strategy to structure the research question. Bibliographic surveys were carried out using the MEDLINE, Lilacs, BDENF, SciELO and PubMed databases using the following terms according to DeCS: "Clinical Protocols", " Extravasation of Therapeutic and Diagnostic Materials", "Oncology Nursing", "Patient Safety", "Antineoplastics". After applying the inclusion and exclusion criteria, 25 articles were selected, read in full, classified and organized according to the theme, and critically analyzed. Results: From the analysis of the studies, it was possible to delimit the main actions and knowledge of nurses in the management and guarantee of patient safety in the face of antineoplastic extravasation, as well as promising new managements in the prevention and treatment of this aggravation. Conclusion: Nurses' knowledge of specific measures for antineoplastic drug leakage is incipient, and there is a clear need for research to minimize the gaps in innovative knowledge in nursing practice with the aim of preventing extravasation.